Wireless Networks for Body-Centric Communications - Martelli, Flavia <0001> (Alma Mater Studiorum - Università di Bologna, 2013)
Progress in miniaturization of electronic components and design of wireless systems paved the way towards ubiquitous and pervasive communications, enabling anywhere and anytime connectivity. Wireless devices present on, inside, around the human body are becoming commonly used, leading to the class of body-centric communications. The presence of the body with all its peculiar characteristics has to be properly taken into account in the development and design of wireless networks in this context.